Grisel syndrome, sigmoid sinus thrombosis and rheumatic carditis: Case report of a rare association. (February 2020) - Cucuzza, Maria Elena; D'Ambra, Angela; Evola, Francesco Roberto; Greco, Filippo; Smilari, Pierluigi
Abstract: Grisel's syndrome (GS) is a non traumatic atlanto-axial rotatory subluxation of C1–C2 joint. A six year old girl, 20 days after an episode of fever, developed a torticollis and a 3/6 heart murmur. The echocardiography showed a Rheumatic Carditis. The Brain and cervical spine Magnetic resonance imaging (MRI) and the Computerized Tomography (CT) showed rotary dislocation of C1–C2 vertebrae, compatible with GS, and cerebral venous thrombosis (CVT). An antibiotic therapy, Prednisone and a low molecular weight heparin for 7 days was prescribedfollowed by an oral anticoagulant for 6 months. After a month the MRI showed a reduction of the dislocation and cerebral venous recanalization.